Calculating 14C mean residence times of inorganic carbon derived from oxidation of organic carbon in groundwater using the principles of 87Sr/86Sr and cation ratio mixing. (15th December 2019) - Magnone, Daniel; Richards, Laura A.; van Dongen, Bart E.; Bryant, Charlotte; Evans, Jane A.; Polya, David A.
Highlights: A new approach to calculate the age of oxidised organic carbon (OC) is developed. Proportions of sources of inorganic carbon (IC) are determined. The case study demonstrates IC from the oxidation of OC in a silicate Holocene aquifer. Radiocarbon adjustment shows IC from the oxidation of OC significantly younger than bulk IC. Abstract: The model radiocarbon age of inorganic carbon (IC) in groundwater is a key parameter for understanding groundwater chemical history and physical parameters such as groundwater residence times and flow rates. Current interpretations are based on the principle that bulk IC derives from multiple sources such as oxidation of organic carbon (OC), carbonate dissolution, and soil zone processes as well as from rainwater. Using this principle, multiple adjustment methods have been developed to calculate rainwater-related recharge ages. Of further interest, however, is the radiocarbon age of oxidised OC. This is a key measurement given that OC oxidation controls the mobility of many important geochemical components such as Fe, As, Mn and U. In this instance, conventional approaches tacitly assume that the majority of IC comes from the oxidation of OC and that other sources have a negligible effect on the bulk age. In reality, however, there are multiple sources of IC which can all effect bulk radiocarbon ages. We present a new approach to calculate the age of IC derived from a specific source. This approach uses strontium isotopes ( 87 Sr/ 86 Sr) coupled with elemental ratios to trace and quantify the mixing of different sources of IC. We demonstrate the approach by calculating the model radiocarbon age of IC sourced from the oxidation of OC for a case study of an aquifer in the Cambodian lowlands located adjacent to the Mekong river south of Phnom Penh. The results show that, although bulk IC is younger and more isotopically (δ 13 C) depleted than bulk organic carbon (OC), IC derived from oxidation of OC has a similar age and isotopic signature to bulk OC. Furthermore, at our site, the age of the IC formed from the oxidation of organic carbon predates modelled groundwater flow by at least a millennium indicating that in-aquifer oxidation is an important process, something previously questioned at the site. This highlights the utility of the new approach to disentangling the origin of the sources of bulk IC, so critical to the interpretation of its model radiocarbon age and isotopic signature.